Educación en la Red: Virtual repository containing interactive experiments for statistics education - Equipo Editor (UNIÓN - REVISTA IBEROAMERICANA DE EDUCACIÓN MATEMÁTICA, 2013)
Educación en la Red:Virtual repository containing interactive experiments forstatistics education